PENERAPAN BALANCED SCORCECARD UNTUK MENINGKATKAN KINERJA BANK MANDIRI CABANG TELUK BETUNG - Sri Risma Yenny; Yuliana - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
This study aimed to analyze the implementation of the Balanced Scorecard as aperformance measurement in Telok Betong branch of Mandiri Bank. This study using descriptivestatistics methods of 4 (four) relevant measurement, that are: 1. financial perspective, using ROAdan ROE, 2. Customer perspective with Customer Retention, Customer Acquistion and CustomerSatisfaction Index. 3. Internal business process perspective measured using Manufacturing CycleEfficiency (MCE). 4. Learning and Growth Perspective using Absenteeism, Employee Training andEmployee Satisfaction Indeks.The results of this study concluded that the Balanced Scrocecard is a comprehensiveperformance measurement for executives and management , laying out the strategic objectives ofthe Bank in some set of performance benchmarks that are logically related to one another.Furthermore Balanced Scorecard helps managers understand the reciprocal relationship ofthe four perspectives, and functions to evaluate a wide range of activities till it can detect the activitywhich led to the decline of the company's performance at the same time take corrective measures.